Treatment of distal femur fractures with VA-LCP condylar plate: A single trauma centre experience. (August 2020) - Campana, V.; Ciolli, G.; Cazzato, G.; Giovannetti De Sanctis, E.; Vitiello, C.; Leone, A.; Liuzza, F.; Maccauro, G.
Abstract: Introduction: Given the recent criticisms in the literature regarding Synthes Variable Angle Locking Compression Condylar Plate (VA-LCP), the purpose of this study was to evaluate functional outcome, fracture healing, and complications of distal femoral intra-articular fractures using this device. Methods: Patients with distal femoral fractures treated with 4.5 mm VA-LCP Curved Condylar Plate were included in this retrospective study. Follow-ups were at 4 weeks, 3 months, 6 months and 1 year. For the clinical and functional assessment of the knee, WOMAC, Koos Knee Survey, the Knee Score Society and the SF-12 questionnaire were used. Radiographically we assessed the fracture healing and the angles of the operated limb compared to the healthy contralateral limb. Complications have also been described. Results: Forty-two patients with distal femoral fractures were included in the study. The mean follow-up was 8 months. Most cases (57%) reported a type 33-A fracture. Radiological healing was achieved in 33 cases; the mean time required to heal was 13 weeks. Three patients had an early postoperative complication and four cases had a late complication. Five cases required additional surgical procedures. Most patients (47.2%) achieved a complete flexion of 130° or more. WOMAC mean value 27.4%, KSS mean value 77.6 for the clinical part and 60 for the functional part, KOOS mean score 60.1, SF-12 mean score 46.1 for MCS and 35.5 for PCS. Discussion: The results of this retrospective study suggest that VA-LCP Curved Condylar Plates have a good functional outcome and fracture healing similar to other standard distal femoral locking plates. VA technology allows greater versatility in fractures internal fixation regardless of the plate design. Fixation devices or Prosthesis implants previously placed may be avoided, as in periprosthetic fractures. Moreover, we have not recorded any early mechanical damage. Conclusions: Osteosynthesis with Synthes 4.5 mm VA-LCP Curved Condylar Plate demonstrated to have no early mechanical failure rate with good clinical and radiological results.